Toxoplasma gondii: disseminação de parasitos, histopatologia e resposta imune celular em um modelo experimental agudo de reinfecção com cepas atípicas - Julia Gatti Ladeia Costa (2016)
Animal model of Toxoplasma gondii reinfection has been studied after cases of natural human reinfection were described. Brazil is an endemic area for toxoplasmosis with enormous genetic diversity of parasites. Multiples exposures with different strains likely occur with great frequency, increasing reinfection risk. Although animal model prove reinfection, little is known about the events that occur just after challenge. To better understand these events, BALB/c mouse were chronically infected with D8 strain (genotype ToxoDB#8 BrIII) and challenge with two different strains: EGS (genótipo ToxoDB #229) and CH3 strain (genotype ToxoDB #19) or with D8 strain. The results were compared to acute infection of each strain and also compared to D8 chronic infection. Primary infection protects animals from lethal challenge. Morbidity was reduced in reinfected mice as demonstrated by monitoring the weight and organs histology showing that pathological changes were minimized. Reinfection was confirmed however different parasite spread occurs in challenge animals. A parasitism delay in brain and intestine has been observed and parasites early reached the lungs. Unlike acute infection, inflammatory or immunomodulatory cytokine increase was not observed in sera or ileum of challenge group. Other immune response mechanisms must be involved in host parasite balance that allows the survival of both. ROP16 virulence protein analysis support understanding about high inflammation caused by EGS strain infection. Nevertheless combined analysis of ROP5 and ROP18 did not proper to predicted virulence in one of three strains used in this study.